Host-Directed Therapeutic Strategies for Tuberculosis - Kolloli, Afsal; Subbian, Selvakumar (Frontiers in Medicine, 2017)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a leading cause of morbidity and mortality in humans worldwide. Currently, the standard treatment for TB involves multiple antibiotics administered for at least six months. Although multiple antibiotics therapy is necessary to prevent the development of drug resistance, the prolonged duration of treatment, combined with toxicity of drugs, contributes to patient non-compliance that can leads to the development of drug-resistant Mtb (MDR and XDR) strains. The existence of co-morbid conditions, including HIV-infection, not only complicates TB treatment but also elevates the mortality rate of patients. These facts underscore the need for the development of new and/or improved TB treatment strategies. Host-directed therapy (HDT) is a new and emerging concept in the treatment of TB, where host response is modulated by treatment with small molecules, with or without adjunct antibiotics, to achieve better control of TB. Unlike antibiotics, HDT drugs act by directly modulating host cell functions; therefore, development of drug resistance by infecting Mtb is avoided. Thus, HDT is a promising treatment strategy for the management of MDR- and XDR-TB cases as well as for patients with existing chronic, co-morbid conditions such as HIV infection or diabetes. Functionally, HDT drugs fine-tune the antimicrobial activities of host immune cells and limit inflammation and tissue damage associated with TB. However, current knowledge and evidence is insufficient to implement HDT alone, without adjunct antibiotics, as therapeutic modality for any form of TB. In this review, we discuss the recent findings on small molecules that target autophagy, vitamin D pathway, and anti-inflammatory response as host-directed adjunctive agents along with standard antibiotics for TB therapy. Data from recent publications show that this approach has the potential to improve clinical outcome and can help to reduce treatment duration. Thus, HDT can contribute to global TB control programs by increasing the efficiency of anti-TB treatment.